Clinical study of ectopic pregnancy - Chate, Meenakshi T.; Chate, Bhagyashree; Chate, Kranti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy is pregnancy that develops following implantation anywhere other than the endometrial cavity of uterus. Objective of present study was to investigate the risk factors, clinical presentation and sites of ectopic pregnancy along with management and assessment of risk of maternal mortality and morbidity. Methods: The study was undertaken at Dr. Shankar Rao Chavhan Government Medical College and Guru Govind singhji hospital, Nanded between December 2012 and May 2014 after obtaining clearance from the Hospital Ethical Committee. Results: Maximum incidence of tubal gestation occurred between the age group of 21-25 years. Greater incidence was noted in multiparous woman. Tubectomy was the most common risk factor seen in 23.65% cases. The most common symptom observed is abdominal pain seen in 92.47% cases. The most common site of ectopic was ampulla seen in 51.61% cases. The most common mode of presentation was rupture seen in 71 cases about 76.35% cases. Unilateral salpingectomy was done in 70 cases about 75.26% cases. Conclusions: Since ectopic pregnancy remains a gynecological catastrophe in countries and a major challenge to the reproductive performance of women worldwide, it should be considered a relevant public health issue. With its rising incidence, which is likely to continue increasing because of the various factors discussed, it is necessary to devise means of early detection and treatment.